Evaluasi Stabilitas Keuangan dan Pengelolaan Risiko Pada Perusahaan Asuransi Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Yudha, Awaludin; Sandi Yuda, Mulfi; Hardianto, Ade Manggala; Novitasari, Yuli (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
The research method used was descriptive quantitative, with secondary data obtained from insurance companies' financial reports published on the Indonesia Stock Exchange (IDX). The results indicate that the sampled insurance companies generally have a healthy and stable financial condition. Liquidity and solvency ratios are within safe limits, while profitability and underwriting tend to be positive. These findings demonstrate that insurance companies are able to adapt to market dynamics and the risks they face, and emphasize the importance of effective risk and fund management for the sustainability and growth of insurance companies in Indonesia.